Pengembangan Sistem Informasi Video Conference Menggunakan Metode Rapid Application Development Berbasis Website - Darmansah, Darmansah; Nengsih, Yeyi Gusla (Forum Kerjasama Pendidikan Tinggi, 2022)
Technological advances can also make it easier to communicate, by conducting video conferences, it is no longer necessary to meet in person during meetings. There have been many platforms used for conducting meetings, but having your own application within the agency or company can be more effective and efficient and data security in the agency is also maintained. At this time, the Yogyakarta Communication and Information Office does not yet have its own meeting application. Based on these problems, the author proposes a video conference information system design for meetings at the Yogyakarta Information and Communications Office. The design uses the RAD method and uses UML (Unified Modeling Language) modeling which consists of use case diagrams, activity diagrams, sequence diagrams and class diagrams. The results of this study resulted in a website that could be used for video conferencing by related agencies.